Identification of the Gene sxtA (Domains sxtA1 and sxtA4) in Mexican Strains of Gymnodinium catenatum (Dinophyceae) and Their Evolution - Mendoza-Flores, Armando; Leyva-Valencia, Ignacio; Band-Schmidt, Christine J.; Galindo-Sánchez, Clara E.; Bustillos-Guzmán, José J. (Frontiers in Marine Science, 2018)
Saxitoxin (STX) and its analogs are a broad group of natural neurotoxic alkaloids, commonly known as paralytic shellfish toxins. SxtA is the initial gene in the biosynthesis of saxitoxin. It has been proposed that the genes for STX biosynthesis had a bacterial origin and were acquired in the dinoflagellates by a horizontal gene transfer (HGT). In Gymnodinium catenatum, the origin of the STX genes is not well established. In this paper, we sequenced sxtA gene (domains sxtA1 and sxtA4) and determined the gene copy number in the genome in four Mexican strains of G. catenatum. We compare them with sequences of G. catenatum, Pyrodinium bahamense, and Alexandrium spp. from other geographic regions, and non-toxic producing dinoflagellates. Amplifications were performed for domains sxtA1 and sxtA4 from strains of G. catenatum and the phylogenetic analyses was done by maximum likelihood and Bayesian inference. The copy number determination was carried out using qPCR. The phylogenetic tree of domain sxtA4 showed the formation of two clades where G. catenatum sequences separated from the Alexandrium/Pyrodinium clade. The domain sxtA1 formed a higher number of clades than sxtA4. Sequences of G. catenatum were grouped together with sequences of Alexandrium. Dinoflagellates sequences that do not produce saxitoxin formed a separate clade. The gene copy number was 64 ± 30 and 110 ± 50 copies of sxtA1 and sxtA4 respectively. The identification of the gene sxtA of G. catenatum shows that the sequences are similar to those of Alexandrium species with low variations between species. These results may indicate that the acquisition of the gene sxtA was an early HGT event in the evolution of dinoflagellates. The possible loss of the ability to produce STX in some species suggests that the HGT from Alexandrium species towards G. catenatum is not possible.